Formation and development of the system of professional training of public servants in ukraine: organizational, legal, and economic aspects - Goncharuk, Nataliia; Orhiiets, Oxana; Prokopenko, Leonid (My University, 2021)
The subject of the research is the formation and development of the system of professional training of public servants in Ukraine. The relevance of this study is due to the fact that one of the most important tasks of the development of the public service institute in modern conditions is its professionalization, which is carried out primarily through the system of professional training of public servants. Methodology. The paper uses a historical approach, which has made it possible to study the process of formation and development of the system of professional training of public servants in Ukraine. Based on the method of systemic analysis, the current system of professional training of civil servants in Ukraine, its legal framework and strategic priorities for its reform are considered. Results. The purpose of the article is to analyze the process of formation and development of the system of professional training of public servants and ways to increase its efficiency in Ukraine in modern conditions. To achieve this goal, the following research objectives are set: to consider the evolution of the system of professional training of public servants in Ukraine; to analyze the development of the system of professional training of public servants in independent Ukraine; to determine the main directions of its reform in the modern conditions of state formation. The main stages of formation and development of the system of professional training of public servants in Ukraine are justified. The organizational, legal, and economic aspects of formation and development of the system of professional training of public servants in Ukraine, as well as regulatory bases of formation and development of competence of public servants are analyzed. It is established that its financial and resource provision is important for the development of the system of professional training of public servants. Emphasis is placed on the need for continuous professional training of civil servants for their mobility, prompt and effective response to societal challenges in a paradigm of public administration, local government reform and decentralization of power in Ukraine through the development of formal, non-formal and informal education. It is concluded that ensuring the effective operation of public servants directly depends on increasing the level of their competence through professional training. The strategic principles of development of the system of professional training of civil servants are analyzed and the ways of increasing the efficiency of the existing system of professional training of civil servants, heads of local state administrations, their first deputies and deputies, local self-government officials, and deputies of local councils are determined, and the new model of the system of professional education of public servants, which based on European principles and standards for the development of adult education for life, are proposed.
Keywords: public administration; public service; public servants; professional training; professional training system; professional development; European educational standards; efficiency of the professional training system for public servants